2019
DOI: 10.1038/s41598-019-42693-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Near Infrared Transcranial and Intranasal Photobiomodulation Significantly Modulates Neural Oscillations: a pilot exploratory study

Abstract: Transcranial photobiomodulation (tPBM) is the application of low levels of red or near-infrared (NIR) light to stimulate neural tissues. Here, we administer tPBM in the form of NIR light (810 nm wavelength) pulsed at 40 Hz to the default mode network (DMN), and examine its effects on human neural oscillations, in a randomized, sham-controlled, double-blinded trial. Using electroencephalography (EEG), we found that a single session of tPBM significantly increases the power of the higher oscillatory frequencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 58 publications
(58 reference statements)
9
103
0
Order By: Relevance
“…Third, 40-Hz pulse rate could enhance the brain gamma waves; similar enhancement with visible spectrum was demonstrated and shown to decrease amyloid-β (Aβ) levels and tau phosphorylation in an animal model of AD (Iaccarino et al, 2016). Portable i-PBMT devices, specifically for the 40-Hz PW mode, were tested to improve concentration and cognitive functioning in AD patients (Chao, 2019) and to modulate neural oscillations in healthy individuals (Zomorrodi et al, 2019). Fourth, PD patients treated with 60-Hz frequency deep brain stimulation have shown significant improvements in swallowing and in motor symptoms (Xie et al, 2015).…”
Section: Intranasal Photobiomodulation Therapy From the Nostrilsmentioning
confidence: 91%
“…Third, 40-Hz pulse rate could enhance the brain gamma waves; similar enhancement with visible spectrum was demonstrated and shown to decrease amyloid-β (Aβ) levels and tau phosphorylation in an animal model of AD (Iaccarino et al, 2016). Portable i-PBMT devices, specifically for the 40-Hz PW mode, were tested to improve concentration and cognitive functioning in AD patients (Chao, 2019) and to modulate neural oscillations in healthy individuals (Zomorrodi et al, 2019). Fourth, PD patients treated with 60-Hz frequency deep brain stimulation have shown significant improvements in swallowing and in motor symptoms (Xie et al, 2015).…”
Section: Intranasal Photobiomodulation Therapy From the Nostrilsmentioning
confidence: 91%
“…[45][46][47][48][49] PBM also affects the cytoskeleton of other cells besides neurons, such as epithelial cells, 50 keratinocytes, 51 and fibroblasts, 52 and has been shown to have effects on protein conformation, including calcium ion channels. [53][54][55] PBM also has an effect on brain oscillation patterns, with changes to alpha, beta, gamma, delta, and theta waves in both mice 56 and humans 57 (El Khoury, et al, unpublished observations) and effects on the default mode network. 58 Many of the diseases treated by PBM are localized by nature and include orthopedic conditions, such as inflammation in joints and tendons, wounds, and fractures.…”
Section: Photobiomodulationmentioning
confidence: 99%
“…There is some evidence that all these seemingly diverse conditions can be bene¯cially a®ected by applying light to the head. 4,[10][11][12] There is even the possibility that PBM could be used for cognitive enhancement in normal healthy people. 27,34 In this transcranial PBM (tPBM) application, near-infrared (NIR) light is often applied to the forehead because of the better penetration (no hair, longer wavelength).…”
Section: Subjectsmentioning
confidence: 99%
“…11 Using an 810 nm NIR light pulse at 40 Hz, Zomorrodi et al found that a single session of tPBM signi¯cantly increased the power of the subjects' alpha, beta and gamma frequencies and decreased the power of delta and theta frequencies in the resting state. 12 Blanco et al 13 used a speci¯c wavelength laser (1064 nm) to explore whether transcranial laser stimulation improved the performance of the Wisconsin Card Sorting Task (WCST). These results showed that subjects receiving laser treatment had fewer errors than the placebo controls and showed improved set-shifting ability.…”
Section: Introductionmentioning
confidence: 99%